A novel NAC family transcription factor SPR suppresses seed storage protein synthesis in wheat. Issue 5 (4th January 2021) - Shen, Lisha; Luo, Guangbin; Song, Yanhong; Xu, Junyang; Ji, JingJing; Zhang, Chi; Gregová, Edita; Yang, Wenlong; Li, Xin; Sun, Jiazhu; Zhan, Kehui; Cui, Dangqun; et al.
Summary: The synthesis of seed storage protein (SSP) is mainly regulated at the transcriptional level. However, few transcriptional regulators of SSP synthesis have been characterized in common wheat ( Triticum aestivum ) owing to the complex genome. As the A genome donor of common wheat, Triticum urartu could be an elite model in wheat research considering its simple genome. Here, a novel NAC family transcription factor TuSPR from T. urartu was found preferentially expressed in developing endosperm during grain‐filling stages. In common wheat transgenically overexpressing TuSPR, the content of total SSPs was reduced by c . 15.97% attributed to the transcription declines of SSP genes. Both in vitro and in vivo assays showed that TuSPR bound to the cis ‐element 5′‐CANNTG‐3′ distributed in SSP gene promoters and suppressed the transcription. The homolog in common wheat TaSPR shared a conserved function with TuSPR on SSP synthesis suppression. The knock‐down of TaSPR in common wheat resulted in 7.07%–20.34% increases in the total SSPs. Both TuSPR and TaSPR could be superior targets in genetic engineering to manipulate SSP content in wheat, and this work undoubtedly expands our knowledge of SSP gene regulation.